Case report: Flexor carpi ulnaris tendinopathy in a lure-coursing dog treated with three platelet-rich plasma and platelet lysate injections - Franini, Alessio; Entani, Maria Grazia; Colosio, Elisa; Melotti, Luca; Patruno, Marco (Frontiers in Veterinary Science, 2023)
In the present case report a 7-year-old male Whippet competing in lure-coursing presented with third-degree recurrent lameness of the right forelimb, pain on palpation of the caudal aspect of the carpus and swelling of the forearm proximally to the accessory carpal bone. Clinical, radiographic, and ultrasonographic evaluation diagnosed a flexor carpi ulnaris (FCU) chronic tendinopathy unresponsive to previously attempted conservative treatments such as oral nonsteroidal anti-inflammatory drugs (NSAIDs) administration along with padded palmar splint application and rest. The dog was subjected to one injection of autologous platelet-rich plasma (PRP) obtained using a double centrifugation tube method, followed by two platelet lysate (PL) injections. Treatment was administered at three-week intervals. The healing process was assessed through clinical and ultrasonographic imaging (US) on the day of the first injection (T0), and at week three (T1), six (T2), twelve (T3), fifty-two (T4), and one-hundred-and-four (T5). Fiber alignment score (FAS) and echogenicity score (ES) were developed by modifying a previously published US assessment scale. At T1, ES and FAS improvement was detected, and at T2, further improvements in ES and FAS were observed. Ultrasonographic results were clinically consistent with the improvement in lameness: lameness grade 3/4 was detected at T0 and grade 2/4 at T1. A lameness grade of 1/4 was detected at T2, and grade 0/4 was observed at T3, T4, and T5. Moreover, at T5, the dog returned to competition, and no history of re-injury was reported. Our results suggest that the treatment of FCU tendinopathy in lure-coursing dogs with a combination of consecutive injections of autologous PRP and PL could be feasible. Additionally, no adverse reactions were observed.